Implementasi Kebijakan Pengelolaan Sampah Oleh Dinas Lingkungan Hidup Aceh Barat - Agatha Debby Reiza Macella; Nur Azima (Program Studi Administrasi Negara Universitas Serang Raya, 2024)
This study aims to examine the Implementation of Household Waste Management Policy by the West Aceh District Environmental and Sanitation Service. This study also discusses what are the obstacles in its implementation and suggestions for solving all the challenges faced. This study used a qualitative research method with a descriptive approach and in this study the authors also used a case study type of research. In collecting data the authors used the method of observation, interviews, as well as documentation and data analysis techniques using data reduction methods, data presentation, and drawing conclusions. The results of the research show that the Implementation of Waste Management Policy, especially Household Waste in West Aceh District, has been carried out by West Aceh DLH, this is evident from the fulfillment of all collaborative indicators according to Van Horn and Van Meter. The obstacles faced in its implementation were internal and external constraints. The internal obstacles faced are understanding of human resources, facilities and infrastructure that are outside the responsibility of DLH, mutations of employees/tasks and external constraints faced are the character of the community. Keyword: Implementation; Policy; Waste Management